The Role of Tax Incentives as A Fiscal Stimulus to The Tax Base and Income Tax Revenue Realization - Ilhamsyah Ilhamsyah; Lela Nurlaela Wati; Etty Puji Lestari (Research Synergy Foundation, 2023)
The government's tax incentives can act as a fiscal stimulus to overcome and accelerate national economic recovery by allocating a tax-spending budget. However, it can lead to the impact of losing the tax base and decreasing the income from tax revenues. This study aims to analyze the effect of tax incentives on the tax base and the realization of income tax revenue. The sample comprised 142 taxpayers who applied for tax incentives due to the COVID-19 outbreak at Kantor Pelayanan Pajak (KPP) Pratama Pangkalan Kerinci, Riau, Indonesia, in 2020 and 2021. The data were analyzed using path analysis techniques. The analysis concludes that the tax base can mediate the tax incentive with the realization of income tax revenue, where tax incentives have a direct negative and significant relationship to the realization of income tax revenue through the tax base. If the government increases the value of the tax incentives, it will directly result in a decrease in the realization of income tax revenue due to taxes paid on the tax base. The research findings implicate that providing tax incentives can increase the tax base in several business sectors, such as health services and plantations. Tax incentives can also increase the aggregate utility of the economy, marked by a large consumption of goods or services. Previous researchers have never conducted this research and provided references regarding tax incentive policies and their impact on tax bases and the realization of tax revenues.